Negative Morphemes in Nsukka Igbo - Comfort Nwuka Ezebuilo, Ph.D (Zien Journals, 2023)
This paper examines negative morphemes in Nsukka-ḷdẹkẹ Igbo, with a view to highlighting significant characteristics of negation in the dialect. As such, the study also aims to investigate the basic characteristics of negation in ḷdẹkẹ dialect of Igbo with particular focus on the selectional restriction observed in their distribution. The study provides within the scope of its size, a more comprehensive and insightful grammatical description of the dialect’s negative morphemes. The study adopts a descriptive survey method as research design and analyses its data descriptively. The databases for the study were drawn from primary sources through informal oral interview and introspection because, the researcher is a native speaker of the dialect. Findings reveal that ḷdẹkẹ dialect employs four different morphemes in marking negation. They are: the widest distributed negative suffix -gu, the past negative suffix -dígu, the negative perfective suffix -legu, and the negative imperative suffix -le. In these negative morphemes, -gu, - diguand –legu are realised as –gǝ, -dǝgǝ and lẹgǝ respectively in the dialect. The variants are the allomorphs of –gu, -digu and –legu. The study observes that the past negative suffix (-digu) is hosted only by the root verbs and is never found on the auxiliary verb. Similarly, the negative perfective suffix (-legu) is also hosted by the verb root and could be attached to the auxiliary verbs in the dialect, particularly where the construction is responding to question(s) negatively. The study also discovered that the negative imperative mood suffix (-le) is phonologically conditioned as opposed to what is obtainable in the Standard Igbo, where the negative imperative mood suffix (-la) is invariant irrespective of the Advanced Tongue Root (ATR) pattern of the vowel in the verb where it is hosted. The above observations infer that the dialect under consideration has a genius of its own, which any analyst must approach in his or her analysis with no presuppositions from his/her knowledge of Standard Igbo.
Keywords: Negation; Morpheme; Nsukka-ḷdẹkẹ